Building Economic Resilience Based on Social Capital: Creativity of Village Communities in Sleman Regency Facing Disaster - Suswanta, Suswanta; Yuliantini, Lisa Sophia (Research Parks Publishers, 2024)
The issue of natural and non-natural disasters is not just security and health but also social and economic issues. Sleman is a district in the Special Region of Yogyakarta, which borders one of the most active volcanoes in the world, namely Merapi. This article aims to explain the strategy of village communities in Sleman district to build economic resilience in facing the eruption of Mount Merapi and COVID-19 by using the concepts of social capital and financial resilience. The research method uses a qualitative descriptive approach using Nvivo 12plus to analyze data. The results show that the economic resilience of village communities in Sleman, especially Umbulharjo Village, Kepuharjo Village, and Glagaharjo Village during the Merapi eruption and Covid-19 disaster, was built due to the existence of strong social capital, namely mutual Trust, mutual understanding, and shared values. The adaptive capacity developed by village communities in Sleman through social capital created resilience, flexibility, and stability in facing the Merapi eruption and COVID-19 disasters.